Corporate governance of banks: A German alternative to the "standard model" - Hans-Helmut Kotz; Reinhard H. Schmidt (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2017)
The paper provides an overview and an economic analysis of the development of the corporate governance of German banks since the 1950s, highlighting peculiarities - as seen from the meanwhile prevailing standard model perspective - of the German case. These peculiarities refer to the specific German notion and legal-institutional regime of corporate governance in general as well as to the specific three-pillar structure of the German banking system. The most striking changes in the corporate governance of German banks during the past 50 years occurred in the case of the large shareholder-owned banks. For them, capital markets have become an important element of corporate governance, and their former orientation towards the interests of a broadly defined set of stakeholders has largely been replaced by a one-sided concentration on shareholders' interests. In contrast, the corporate governance regimes of the smaller local public savings banks and the local cooperative banks have remained virtually unchanged. They acknowledge a broader horizon of stakeholder interests and put an emphasis on monitoring. The Great Financial Crisis, beginning in 2007, has led to a considerable reassessment in the academic and political debate on bank governance. On an international level, it has revived the older notion that, in view of their high leverage and their innate complexity, banks are "special" and bank corporate governance also - and needs to be seen in this light, not least because research indicates that banks with a strong and one-sided shareholder orientation - and thus with what appears to be the best corporate governance according to the standard model - have suffered most in the crisis. In the German case, the crisis has shown that the smaller local banks have survived the crisis much better than large private and public banks, whose funding strongly depends on wholesale markets. This may point to certain advantages of their governance and ownership regimes. But the differences in the performance during the crisis years may also, or even more so, be a consequence of the business models of large vs small banks than of their different governance regimes
urn:nbn:de:hebis:30:3-438869
Keywords: 330; corporate governance; German banks; German banking system